Relationship Between Subjectively Evaluated Health and Fear of Death Among Elderly in Three Cultural Contexts: Effects of Internal and External Resources. (April 2017) - Hofer, Jan; Busch, Holger; Šolcová, Iva Poláčková; Tavel, Peter
It is often argued that declining health in elderly people makes death more salient and threatening. However, we argue that health, optimism, and social support interact to predict fear of death in samples from Cameroon, the Czech Republic, and Germany. Low health was associated with enhanced fear of death for participants who received only little social support. As the measure of optimism did not comply with psychometric requirements in the Cameroonian sample, the three-way interaction was tested only in the Czech and German samples. It was found that the two-way interaction was further qualified by optimism in that low health was associated with enhanced fear of death for participants with little social support unless they reported pronounced optimism. Thus, internal and external resources, respectively, can serve to buffer the effect of declining health on the fear of death in the elderly.